2020
DOI: 10.1115/1.4046925
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Improvement of a Centrifugal Compressor Based on Partial Similarity Principle

Abstract: In this paper, with the help of partial similarity principle, aerodynamic performance of a centrifugal compressor in a turbocharger unit is analyzed and improved based on a low-speed large-scaled model. In order to achieve flow similarity between the scaled compressor and the prototype, tip clearance and diffuser outlet diameter have been modified further. It is observed from the numerical results that the relative error between the scaled compressor and the prototype is less than 0.8%. It means that the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Scaling a prototype compressor, sometimes, is beneficial to reduce both the difficulty and cost of the experiment. 15 Dufour et al 16 reported the practical use of geometrical scaling of an existing impeller and proved the feasibility of the scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling a prototype compressor, sometimes, is beneficial to reduce both the difficulty and cost of the experiment. 15 Dufour et al 16 reported the practical use of geometrical scaling of an existing impeller and proved the feasibility of the scheme.…”
Section: Introductionmentioning
confidence: 99%